76 MATCHED CASE-CONTROL STUDY OF QUALITY OF LIFE AND XEROSTOMIA AFTER INTENSITY MODULATED OR STANDARD RADIOTHERAPY FOR HEAD AND NECK CANCER. (1st March 2005) - Murdoch-Kinch, C. A.; Jabbari, S.; Kim, H. M.; Feng, M.; Lin, A.; Tsien, C.; Elshaikh, M.; Terrell, J. E.; Eisbruch, A.
Abstract : Purpose: To compare quality of life (QOL) and xerostomia in head and neck cancer (HNC) patients who received standard radiotherapy (RT) and patients matched by factors known to affect QOL who received parotid-sparing intensity modulated RT (IMRT). Methods: Prospective longitudinal study of HNC patients requiring bilateral neck irradiation who received IMRT and patients who received standard RT. Each subject completed a validated head and neck cancer-related QOL questionnaire (HNQOL) and a validated patient-reported xerostomia questionnaire (XQ) pre-therapy and at 1, 3, 6, 12, 18 and 24 months post-therapy. Answers scored 0-100; higher scores denoted worse QOL or xerostomia. Each standard RT subject was matched with several IMRT subjects according to tumor site, stage, RT status (postoperative or definitive), and age. A linear mixed effects model was fit to compare outcomes between the 2 treatment groups and to model trends over time. To account for matching, differences in scores between the matched sets of patients were fit as a random intercept, and the standard error of the within-paired-groups differences was used. Results: During 1997 - 2002, subjects who received standard RT and completed both questionnaires through at least one year were included in the study (n = 10). Each was matched with a sub-group of 2-5 subjects (median 3) who received IMRT, had similar characteristics, and completed the same questionnaires (n = 30). In initial months after therapy, the XQ and HNQOL summary scores worsened significantly in both groups compared to pre-therapy scores. Starting at 6 months, both XQ and HNQOL scores improved over time in the IMRT subjects (p = 0.01 and 0.04), but not in the standard RT subjects (p = 0.5 and 0.9). At 12 months, median XQ and HNQOL scores were lower (better) in IMRT than standard RT subjects by 19 and 20 points, respectively, adjusted for pre-therapy values (p = 0.2). In both groups pre-therapy XQ and HNQOL summary scores were significantly related to the post-therapy scores (p = 0.02 and p<0.01). Conclusions: After an initial post-therapy decline in both groups, xerostomia and QOL scores improved over time after IMRT but not after standard RT. The potential benefits gained from IMRT in xerostomia or in QOL, compared with standard RT, are best reflected later than 6 months after therapy.